Fractional reserve banking and price stability: Evidence from Gulf Cooperation Council (GCC) countries - Musse, Osman Sayid Hassan; Echchabi, Abdelghani; Abd Aziz, Hassanuddeen (Science Publications, 2015)
This study aims at investigating the possible influence of the current money creation process applied by the commercial banks through the fractional reserve system on the overall prices stability in the Gulf Cooperation Council (GCC) countries. The study uses yearly data spanning from 2008 through 2013 for Qatar, Kuwait, Oman, Saudi Arabia and United Arab Emirates and applies panel regression analysis based on the pooled data set. The results indicate that neither outstanding deposits nor outstanding loans have a significant influence on general price levels.